Camera Trap Evidence of Polymorphic Asiatic Golden Cat (Catopuma temminckii) in Trashigang Forest Division, Eastern Bhutan - Norbu, Lam; Koirala, Bal Krishna; Dechen, Ugyen; Dorji, Tshering; Tshering, Dawa; Dorji, Pasang; Dorji, Lekey; Phuntsho, Ugyen; Lhendup, Ugyen; Tobgay, Sonam; Sherub, Karma (Bhutan Journal of Natural Resources and Development, 2022)
The Asiatic golden cat, Catopuma temminckii, is a medium-sized felinae distributed throughout South Asia. It is currently categorized as Near Threatened on the IUCN Red List and listed in Appendix I by CITES and Schedule I of the Forest and Nature Conservation Act of Bhutan, 1995. The six colour morphs of Asiatic golden cats have been recognized from their geographic range. The present study (2014-2015) was conducted as a part of the third nationwide tiger survey and wildlife monitoring assessments (2017-2021) in the Trashigang Forest Division. We used camera traps as a tool for the survey. The camera trap photographs confirmed the occurrence of five morphs of Asiatic golden cat from the present locality. All five morphs were photographed at altitudes ranging from 2200-3800 m. The results highlight the importance of conserving eastern Himalayan landscapes to ensure the safe refuse to globally threatened felids, including Asiatic golden cat.